Gambaran tingkat pengetahuan ibu tentang pijat bayi 0-3 tahun Di Dusun Pandes 2 Wonokromo Pleret Bantul - Julisia, Gita; Wulandari, Setyo Retno (Jurnal Kesehatan Samodra Ilmu (JKSI), 2021)
ABSTRACT Background : : According to the World Healthy Organization (WHO), 2017, globally, around indonesia, the role od baby massage is still held by traditional develoment proces. In percantage of low birt babies in the province of DIY especially in Bantul Regency reached 4.9%. One of the gevernment’s to overcome childres’s health is a manual technique in the form of massage stimulation. Research methods : This reseaarch is a quantitativ desriptive study. The sampel population in this study were all mother who had babies 0-3 year in pandes 2 wonokromo pleret bantul hamle. The sampling techniqeu in this study is accidental sampling based on chancer or meeting with the researcher. Obtained by 33 respondents. The data was taken using a questionnaire. The analysis method usus unvariate analiysis. Results and discussion : The level of kwonledge of mothers about baby massage 0-3 years is mostly good category 15 people (45.5%), knowledge about massage is mostly eneough category 19 people (57.6%), knowledge about the benefits of baby massage is mostly eneough category 15 people(45.5%), knowledge of the procedures for infant massage in most categories is sufficient for 17 (51.5%), knowledge about the recomended age for massage in most categories is sufficient for 15 people (45.5%).